Cabo Verde : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Cabo Verde. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Cabo Verde's Request for Disbursement Under the Rapid Credit Facility (RCF). Mitigating measures taken by the authorities are aimed at preventing an extensive spread of the pandemic, and helping the private sector, households and vulnerable groups mitigate the fallouts of the pandemic. However, important challenges remain in view of the existing uncovered financing gaps and uncertainties on the duration of the pandemic, calling for financial support from Cabo Verde's development partners. IMF financing under the RCF will provide additional foreign exchange and much-needed budget support. While addressing the impact of the coronavirus disease 2019 pandemic, the authorities should stand ready to resume reforms and policies needed to return the economy to its pre-pandemic medium-term trajectory, anchored in sustained growth, stronger external and fiscal positions, and declining ratio of public debt to gross domestic product. Beyond the crisis, the medium-term outlook remains broadly favorable, under the assumption of a recovery of the global economy, resumption of tourism and capital inflows, and the growth-enhancing reforms envisaged under the authorities' Plan for Sustainable Development.